2022
DOI: 10.3390/buildings12010082
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Energy Consumption in American Homes by Climate Region

Abstract: The present research analyzes the impact of nine factors related to household demographics, building equipment, and building characteristics towards a home’s total energy consumption while controlling for climate. To do this, we have surveyed single-family owned houses from the 2015 Residential Energy Consumption Survey (RECS) dataset and controlled the analysis by Building America climate zones. Our findings are based on descriptive statistics and multiple regression models, and show that for a median-sized h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…A significant factor in the energy balance of residential homes is the energy-saving behaviors of its residents [13,14,38,40]. While energy demands can greatly vary across seasons and geographical locations, heating and cooling determine a large percentage of energy use in households [4][5][6]. One consequential behavior is the selection of temperature setpoints for thermostats [38], which can strongly affect the energy balance of residential homes by determining, under certain conditions, up to 30% of the energy use [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant factor in the energy balance of residential homes is the energy-saving behaviors of its residents [13,14,38,40]. While energy demands can greatly vary across seasons and geographical locations, heating and cooling determine a large percentage of energy use in households [4][5][6]. One consequential behavior is the selection of temperature setpoints for thermostats [38], which can strongly affect the energy balance of residential homes by determining, under certain conditions, up to 30% of the energy use [17].…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed that energy consumption is largely influenced by the climate conditions that the buildings are in [4]. Specifically, outside temperatures [5] and climate zones (i.e., geographical location) [6] significantly affect energy needs and usage. Energy demands and consumption purposes vary greatly across different geographical locations [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study in [17] identified heating equipment type and home size as primary contributors to energy consumption across most climate zones, with variations observed in different regions. Additionally, the influence of on-site solar power generation was found to be limited, suggesting the need for further research and policy considerations [18].…”
Section: Residential Energy Consumption Datamentioning
confidence: 99%
“…Single-family zoning contradicts political goals that aim to increase urban density [6][7][8] and reduce the carbon footprint [9][10][11]. Critics also point to the low energy efficiency of many single-family detached houses [12,13] and the extra costs for roads, sewage, and water infrastructure caused by dispersed settlements [14,15]. Esthetic considerations oppose suburban single-family houses as mass or anonymous architecture [16], which fit poorly into the historically evolved urban fabric.…”
Section: Introductionmentioning
confidence: 99%